Wear-resistant thermoplastic vulcanized rubber material and preparation method thereof

By using compositions of components such as polyolefin elastomers, styrene block copolymers in thermoplastic vulcanized glue materials, combined with twin screw extrusion technology, the difficulty in balancing the wear resistance and tensile strength of existing materials is solved. The problem is that the material has excellent wear resistance and mechanical properties.

CN119119625APending Publication Date: 2024-12-13CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310695207.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

It is difficult for existing thermoplastic vulcanized adhesive materials to achieve a balance between wear resistance and tensile strength, resulting in insufficient performance in the material in practical applications.

Method used

Using a composition composed of polyolefin elastomer, styrene block copolymer, wear-resistant polymer, inorganic filler, crosslinking agent and antioxidant, dynamic vulcanization treatment is carried out through a twin-screw extruder to prepare excellent resistance. Thermoplastic vulcanized glue material with abrasiveness, hardness and fixed stretch strength.

Benefits of technology

It achieves a balance between wear resistance, hardness and tensile strength, improves the overall mechanical properties of the material, and is suitable for high-demand industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004281464890000071
    Figure BDA0004281464890000071
  • Figure BDA0004281464890000081
    Figure BDA0004281464890000081
Patent Text Reader

Abstract

The invention discloses a wear-resistant thermoplastic vulcanized rubber material, a preparation method thereof and a product prepared from the wear-resistant thermoplastic vulcanized rubber material. The wear-resistant thermoplastic vulcanized rubber material is prepared from a composition containing the following components in parts by weight through reaction: 40 to 70 parts of polyolefin elastomer, 30 to 50 parts of styrene block copolymer, 5 to 30 parts of wear-resistant polymer, 0 to 30 parts of inorganic filler, 0.1 to 1 part of cross-linking agent, 0.1 to 1 part of cross-linking aid and 0.01 to 1 part of antioxidant, the sum of the weight of the polyolefin elastomer, the styrene block copolymer and the wear-resistant polymer is 100 parts by weight. The wear-resistant thermoplastic vulcanized rubber material provided by the invention has excellent wear resistance and excellent mechanical strength, and achieves the balance among wear resistance, hardness and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of vulcanized rubber materials, and in particular to a wear-resistant thermoplastic vulcanized rubber material and a preparation method thereof. Background Art

[0002] Thermoplastic vulcanizate (TPV) is a high-performance material with physical properties between rubber and plastic, and has excellent elastic and mechanical properties. TPV has the physical properties and functional characteristics of thermosetting rubber at room temperature, and the high fluidity and reproducibility of thermoplastics at high temperatures, making the product easy to mold, recyclable, and cost-effective. It is currently widely used in the automotive industry, construction materials, electronic appliances and other fields.

[0003] CN112126161A discloses a dynamically vulcanized nylon encapsulated TPV and a preparation method thereof, which is made of EPDM, PP, white oil, grafted PP, grafted POE, grafted SEBS, PA, peroxide, a crosslinking aid, and an antioxidant through a two-step twin-screw granulation method. Due to the addition of the grafted product, the compatibility of the system is enhanced, the PA coating effect is enhanced, and the TPV is resistant to aging.

[0004] CN 104861295 B discloses a method for preparing a modified polypropylene material with improved impact strength. The elastomer raw materials are as follows: polypropylene, polyolefin elastomer, high-density polyethylene, a crosslinking agent and a crosslinking aid. The above materials are processed by extrusion to prepare a new elastomer, and the obtained elastomer has good impact strength, cold resistance and gasoline resistance.

[0005] CN 113637283 A discloses a high-strength and high-resilience TPE thermoplastic elastomer. The raw materials of the elastomer are as follows: hydrogenated styrene thermoplastic elastomer, filler oil, plasticized reinforcing resin, high elastic composition, filler, antioxidant, lubricant and colorant. The above materials are processed by extrusion to prepare a new type of elastomer, and the obtained elastomer has good resilience, mechanical properties, weather resistance and wear resistance.

[0006] CN 112126161 A discloses a dynamically vulcanized nylon encapsulated TPV and a preparation method thereof. The obtained material has good compatibility, but poor tensile strength, and the wear resistance and tensile strength of the product are not tested.

[0007] CN 104861295B discloses a method for preparing a modified polypropylene material with improved impact strength. The obtained material has good impact strength and other properties; however, the wear resistance and tensile strength of the product are not tested.

[0008] CN 113637283A discloses a high-strength and high-elasticity TPE thermoplastic elastomer. The obtained material has good elasticity, but poor tensile strength, and the wear resistance and tensile strength of the material are not tested.

[0009] The above-mentioned prior art does not achieve a balance between wear resistance and tensile strength. Summary of the invention

[0010] In order to solve the technical problems existing in the prior art, the present invention provides a wear-resistant thermoplastic vulcanizate material and a preparation method thereof. The wear-resistant thermoplastic vulcanizate material according to the present invention has excellent wear resistance, hardness and tensile strength, and achieves a balance between wear resistance, hardness and tensile strength.

[0011] According to a first aspect of the present invention, there is provided a wear-resistant thermoplastic vulcanizate material, which is prepared by reacting a composition comprising the following components:

[0012] 40 to 70 parts by weight, preferably 50 to 60 parts by weight of a polyolefin elastomer;

[0013] 30 to 50 parts by weight, preferably 30 to 40 parts by weight of a styrene block copolymer;

[0014] 5 to 30 parts by weight, preferably 5 to 20 parts by weight of a wear-resistant polymer;

[0015] 0 to 30 parts by weight, preferably 0 to 20 parts by weight of an inorganic filler;

[0016] 0.1 to 1 parts by weight of a cross-linking agent;

[0017] 0.1 to 1 parts by weight of a cross-linking aid; and

[0018] 0.01 to 1 parts by weight of an antioxidant,

[0019] The total weight of the polyolefin elastomer, the styrene block copolymer and the wear-resistant polymer is 100 parts by weight.

[0020] Preferably, the wear-resistant thermoplastic vulcanizate material does not contain any softener, for example, the softener may be white oil, paraffin oil and / or naphthenic oil.

[0021] Preferably, the melt flow rate of the polyolefin elastomer at 190°C under a load of 2.16 kg is 0.1 to 2.5 g / 10 min; preferably, the melt flow rate at 190°C under a load of 2.16 kg is 0.3 to 2.0 g / 10 min; more preferably, the melt flow rate of the polyolefin elastomer at 190°C under a load of 2.16 kg is 0.3 to 0.7 g / 10 min.

[0022] Preferably, the polyolefin elastomer is at least one selected from ethylene-octene copolymer (POE), ethylene-propylene copolymer (EPDM), and ethylene-octene block copolymer (OBC).

[0023] Preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, and the styrene content is 20wt% to 50wt%; more preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 100,000, and the styrene content is 25wt% to 40wt%.

[0024] Preferably, the styrene-based block copolymer is at least one selected from styrene / butadiene / styrene block copolymer (SBS) and styrene / ethylene-butylene / styrene block copolymer (SEBS).

[0025] Preferably, the wear-resistant polymer has a Shore hardness of 40D or more; more preferably, the wear-resistant polymer is at least one selected from polyethylene (PE), polypropylene (PP) and acrylonitrile / butadiene / styrene terpolymer (ABS).

[0026] Polyethylene (PE) refers to low-density polyethylene and high-density polyethylene, excluding ultra-high molecular weight polyethylene.

[0027] Preferably, the inorganic filler is at least one selected from ceramic powder, carbon black, alumina, carbon nanotubes and carbon fibers.

[0028] Preferably, the crosslinking agent is at least one selected from di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, 1,4-di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.

[0029] Preferably, the crosslinking aid is at least one selected from trimethylolpropane triacrylate, triallyl isocyanurate and trimethylolpropane trimethacrylate.

[0030] Preferably, the antioxidant is at least one selected from phosphite antioxidants, hindered phenol antioxidants and thioester antioxidants, more preferably, the antioxidant is a hindered phenol antioxidant and a phosphite antioxidant; further more preferably, the antioxidant is at least one selected from antioxidant 245, antioxidant 626, antioxidant 168 and antioxidant 1010.

[0031] Preferably, the wear-resistant thermoplastic vulcanizate material is molded into a 8 mm thick plate by a tablet press and cut into a cylinder with a diameter of 16 mm, and then the wear amount measured by a roller abrasion machine according to the GB / T 9867-2008 method is 150 mm 3 the following.

[0032] Preferably, the wear-resistant thermoplastic vulcanizate material is pressed into a 2 mm thick sheet by a sheet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of more than 18 MPa; and a 300% elongation strength of more than 6.5 MPa.

[0033] Preferably, the wear-resistant thermoplastic vulcanizate material according to the present invention is molded into an 8 mm thick plate by a tablet press, and the Shore hardness obtained by measuring the plate by a hardness tester according to the GB / T6031-2017 method is 75A or more.

[0034] According to a second aspect of the present invention, there is provided a method for preparing a wear-resistant thermoplastic vulcanizate material, comprising the following steps:

[0035] S1: blending a polyolefin elastomer, a styrene block copolymer, a wear-resistant polymer, an inorganic filler and an antioxidant, and then melt-blending and extruding the mixture through a twin-screw extruder, and granulating the mixture to obtain a primary thermoplastic elastomer material;

[0036] S2: The primary thermoplastic elastomer, the crosslinking agent and the crosslinking aid material prepared in step S1 are blended, and then dynamically vulcanized and extruded through a twin-screw extruder to obtain a thermoplastic vulcanizate material.

[0037] Preferably, the conditions for melt blending in step S1 are: extrusion temperature of 180-220° C.; and extruder speed of 200-300 r / min.

[0038] Preferably, the conditions for melt blending in step S2 are: extrusion temperature of 180-220° C.; and extruder speed of 60-150 r / min.

[0039] According to a third aspect of the present invention, there is provided a product, which is prepared from the wear-resistant thermoplastic vulcanizate material according to the present invention.

[0040] The wear-resistant thermoplastic vulcanizate material according to the present invention has excellent wear resistance and excellent mechanical strength, and achieves a balance between wear resistance, hardness and mechanical properties. DETAILED DESCRIPTION

[0041] The testing methods of the relevant performance parameters involved in the following embodiments and comparative examples are as follows:

[0042] 1. Determination of wear

[0043] An appropriate amount of the above thermoplastic vulcanizate material was weighed, molded into a plate with a thickness of 8 mm and cut into a cylinder with a diameter of 16 mm, and then measured using a drum abrasion machine according to the GBT 9867-2008 method.

[0044] 2. Tensile modulus test method

[0045] The weighed composite pellets were pressed into 2 mm thick sheets using a tablet press and cut into standard tensile specimens. After being placed in a test room for 24 hours, the sheets were tested using an Instron 5965 testing machine according to the GB T528-2009 method.

[0046] 3. Determination of hardness

[0047] Weigh an appropriate amount of the above thermoplastic vulcanizate material, mold it into a 8 mm thick plate, and use a hardness tester to measure it according to the GB / T6031-2017 method.

[0048] Material

[0049] Ethylene-octene copolymer (POE), Dow Chemical, brand 8150, melt flow rate 0.5 g / 10 min (190 ° C, 2.16 kg), Mooney viscosity (ML1+4@121 ° C) 33, density 0.868 g / cm 3 ;

[0050] Ethylene-propylene copolymer (EPDM), Dow Chemical, brand 4770P, Mooney viscosity (ML1+4@125℃) is 70, density is 0.87g / cm 3 , the melt flow rate is the melt flow rate is 2g / 10min (190℃, 2.16kg);

[0051] Ethylene-octene block copolymer (OBC), Dow Chemical, brand 9077, density 0.869 g / cm 3 , melt flow rate is 0.5g / 10min (190℃, 2.16kg);

[0052] Styrene block copolymer (SEBS), Sinopec Baling, brand name YH501T, weight average molecular weight 70,000, styrene content 30wt%;

[0053] Styrene / butadiene / styrene block copolymer (SBS), Baling Petrochemical, brand name YH-792, molecular weight 100,000, styrene content 40wt%;

[0054] High-density polyethylene (HDPE), Yanshan Petrochemical, brand 7600M, melt flow rate 0.3g / 10min (190℃, 2.16kg), Shore hardness 63D;

[0055] Polypropylene (PP), Yulin Chemical, brand K8003, melt flow rate 3g / 10min (190℃, 2.16kg), Shore hardness 65D;

[0056] Acrylonitrile / butadiene / styrene terpolymer (ABS), Takahashi Petrochemical, brand 3513, melt flow rate 10g / 10min (190℃, 10kg), Shore hardness 80D;

[0057] Carbon black (CB), brand N330; purchased from Shanghai Kain Chemical Co., Ltd.;

[0058] 1,4-di-tert-butylperoxyisopropylbenzene (BIBP) was purchased from Shanghai Dunmei New Material Technology Co., Ltd.;

[0059] Triallyl isocyanurate (TAIC) was purchased from Shanghai Dunmei New Material Technology Co., Ltd.;

[0060] Antioxidant A was antioxidant 168, purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;

[0061] Antioxidant B was antioxidant 1010 purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;

[0062] The raw materials used in the examples and comparative examples are all commercially available.

[0063] Example 1

[0064] 1) 5.7 kg POE, 3.8 kg SEBS, 0.5 kg HDPE, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0065] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 1.

[0066] Example 2

[0067] 1) 5.4 kg POE, 3.6 kg SEBS, 1 kg HDPE, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0068] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.1 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 180°C. The performance test results are shown in Table 1.

[0069] Example 3

[0070] 1) 5.1 kg POE, 3.4 kg SEBS, 1.5 kg HDPE, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0071] 2) 10 kg of TPE obtained in step 1, 0.1 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 190°C. The performance test results are shown in Table 1.

[0072] Example 4

[0073] 1) 5.4 kg EPDM, 3.6 kg SBS, 1 kg PP, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0074] 2) 10 kg of TPE obtained in step 1, 0.05 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 1.

[0075] Example 5

[0076] 1) 5.4 kg POE, 3.6 kg SBS, 1 kg HDPE, 1 kg CB, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0077] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 1.

[0078] Example 6

[0079] 1) 5.4 kg OBC, 3.6 kg SEBS, 1 kg ABS, 1.5 kg carbon nanotubes, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed mixer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0080] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 1.

[0081] Table 1: Properties of wear-resistant thermoplastic vulcanizates prepared in Examples 1 to 6

[0082]

[0083] Comparative Example 1

[0084] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0085] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 2.

[0086] Comparative Example 2

[0087] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 2.

[0088] Comparative Example 3

[0089] 1) 5.4 kg POE, 3.6 kg SEBS, 1 kg HDPE, 4 kg CB, 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0090] 2) 10 kg of TPE obtained in step 1, 0.1 kg of BIBP and 0.1 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 2.

[0091] Comparative Example 4

[0092] 1) 5.4 kg POE, 3.6 kg SEBS, 1 kg polyvinylidene fluoride (PVDF), 0.01 kg antioxidant A and 0.01 kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0093] 2) 10 kg of TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C. The performance test results are shown in Table 2.

[0094] Table 2: Properties of materials prepared from Comparative Examples 1 to 4

[0095]

[0096] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.

Claims

1. A wear-resistant thermoplastic vulcanizate material, which is prepared by reacting a composition comprising the following ingredients: 40 to 70 parts by weight, preferably 50 to 60 parts by weight of a polyolefin elastomer; 30 to 50 parts by weight, preferably 30 to 40 parts by weight of a styrene block copolymer; 5 to 30 parts by weight, preferably 5 to 20 parts by weight of a wear-resistant polymer; 0 to 30 parts by weight, preferably 0 to 20 parts by weight of an inorganic filler; 0.1 to 1 parts by weight of a cross-linking agent; 0.1 to 1 parts by weight of a cross-linking aid; and 0.01 to 1 parts by weight of an antioxidant, The total weight of the polyolefin elastomer, the styrene block copolymer and the wear-resistant polymer is 100 parts by weight.

2. The wear-resistant thermoplastic vulcanizate material according to claim 1, wherein: The wear-resistant thermoplastic vulcanizate material does not contain any softener.

3. The wear-resistant thermoplastic vulcanizate material according to claim 1 or 2, wherein: The polyolefin elastomer has a melt flow rate of 0.1 to 2.5 g / 10 min at 190° C. under a load of 2.16 kg; preferably, the melt flow rate of 0.3 to 2.0 g / 10 min at 190° C. under a load of 2.16 kg; Preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, and the styrene content is 20wt% to 50wt%; more preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 100,000, and the styrene content is 25wt% to 40wt%.

4. The wear-resistant thermoplastic vulcanizate material according to any one of claims 1 to 3, wherein: The polyolefin elastomer is at least one selected from ethylene-octene copolymer (POE), ethylene-propylene copolymer (EPDM), and ethylene-octene block copolymer (OBC); Preferably, the styrene block copolymer is at least one selected from styrene / butadiene / styrene block copolymer (SBS) and styrene / ethylene-butylene / styrene block copolymer (SEBS).

5. The wear-resistant thermoplastic vulcanizate material according to any one of claims 1 to 4, wherein: The wear-resistant polymer has a Shore hardness of 40D or more; preferably, the wear-resistant polymer is at least one selected from polyethylene (PE), polypropylene (PP) and acrylonitrile / butadiene / styrene terpolymer (ABS); Preferably, the inorganic filler is at least one selected from ceramic powder, carbon black, alumina, carbon nanotubes and carbon fibers.

6. The wear-resistant thermoplastic vulcanizate material according to any one of claims 1 to 5, wherein: The cross-linking agent is at least one selected from di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, 1,4-di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide; Preferably, the crosslinking aid is at least one selected from trimethylolpropane triacrylate, triallyl isocyanurate and trimethylolpropane trimethacrylate; Preferably, the antioxidant is at least one selected from phosphite antioxidants, hindered phenol antioxidants and thioester antioxidants; more preferably, the antioxidant is a hindered phenol antioxidant and a phosphite antioxidant; further more preferably, the antioxidant is at least one selected from antioxidant 245, antioxidant 626, antioxidant 168 and antioxidant 1010.

7. The wear-resistant thermoplastic vulcanizate material according to any one of claims 1 to 6, wherein: The wear-resistant thermoplastic vulcanizate material was molded into a 8 mm thick plate using a tablet press and cut into a cylinder with a diameter of 16 mm. The wear loss was then measured using a roller abrasion machine according to the GB / T 9867-2008 method. 3 the following; Preferably, the wear-resistant thermoplastic vulcanizate material is pressed into a 2 mm thick sheet by a sheet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of 18 MPa or more; a 300% elongation strength of 6.5 MPa or more; Preferably, the wear-resistant thermoplastic vulcanizate material according to the present invention is molded into an 8 mm thick plate by a tablet press, and the Shore hardness obtained by measuring the plate by a hardness tester according to the GB / T6031-2017 method is 75A or more.

8. A method for preparing a wear-resistant thermoplastic vulcanizate material, comprising the following steps: S1: blending a polyolefin elastomer, a styrene block copolymer, a wear-resistant polymer, an inorganic filler and an antioxidant, and then melt-blending and extruding the mixture through a twin-screw extruder, and granulating the mixture to obtain a primary thermoplastic elastomer material; S2: The primary thermoplastic elastomer, the crosslinking agent and the crosslinking aid material prepared in step S1 are blended, and then dynamically vulcanized and extruded through a twin-screw extruder to obtain a thermoplastic vulcanizate material.

9. The method for preparing the wear-resistant thermoplastic vulcanizate material according to claim 8, wherein: The conditions for melt blending in step S1 are: extrusion temperature of 180-220° C.; extruder speed of 200-300 r / min; Preferably, the conditions for melt blending in step S2 are: extrusion temperature of 180-220° C.; and extruder speed of 60-150 r / min.

10. A product prepared from the wear-resistant thermoplastic vulcanizate material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A method for preparing modified polypropylene material with improved impact resistance

    CN104861295B

  • Dynamically vulcanized nylon rubber-coated TPV and manufacturing method thereof

    CN112126161A

  • High-strength high-resilience TPE and preparation method thereof

    CN113637283A